Embodied philanthropy and Sir Captain Tom Moore's "Walk for the NHS". Issue 3 (27th March 2022) - Wade, Matthew; Hookway, Nicholas; Filo, Kevin; Palmer, Catherine
Abstract: Recent decades have witnessed growing popularity in embodied philanthropy, where participants undertake various types of publicly displayed bodily labour in support of their respective causes. The fundraising potential of such efforts reached extraordinary heights during Sir Captain Thomas Moore's "Walk for the National Health Service, " wherein the 99‐year‐old World War II veteran walked laps of his garden to raise funds during the COVID‐19 pandemic. Within less than a month "Captain Tom" raised over £30 million, the highest amount ever by an individual charity walker. To better understand the social and cultural drivers behind Moore's incredible popularity this article applies Julie Robert's theoretical framework of embodied philanthropy, exploring the multivalent semiotic potential that Moore radiated through his age, disability, military adornments, Yorkshire grit, and unfailingly positive, aphoristic style of speaking. During a time of global crisis, this distinct array of bodily affordances enabled Captain Tom to simultaneously serve as an honest broker, teacher, exemplar, rallying figure, and ultimately martyr. Such practices of sacrificial citizenship, however, raise troubling questions, particularly in relation to expectations that fellow citizens should likewise stoically uphold civic‐minded resilience during times of crisis. Furthermore, while the potential benefits can prove extraordinarily impactful, organizations should exercise care in too readily attaching themselves to particular causes, lest they become complicit in contentious agendas or even inadvertently mislead donors.